Glycosylation-Dependent Induction of Programmed Cell Death in Murine Adenocarcinoma Cells - Parshenkov, Aleksei; Hennet, Thierry (Frontiers in Immunology, 2022)
Altered surface glycosylation is a major hallmark of tumor cells associated with aggressive phenotype and poor prognosis. By recognizing specific carbohydrate motifs, lectins can be applied to distinguish tumor from healthy cells based on the expression of glycosylation-dependent markers. Through their ability to bind to specific carbohydrates, lectins induce cell agglutination and cross-link surface glycoproteins, thereby mediating mitogenic and death-inducing effects in various cell types. The carbohydrate-selective cytotoxic effect of lectins also enables their possible application in therapies targeting cancer cells. To clarify the intracellular pathways mediating cell death induced by a group of plant and fungal lectins, we investigated mouse adenocarcinoma MC-38 cells harboring inactive genes involved in apoptosis, necroptosis and pyroptosis. Treatment of MC-38 cells with wheat germ agglutinin, Maackia amurensis lectin I, and Aleuria aurantia lectin induced multiple cell death pathways through reactions that relied on the autophagy machinery without depending on caspase activation. Furthermore, inhibition of de novo protein synthesis by cycloheximide strongly decreased the cytotoxic response, indicating that the lectins investigated induced cell death via effector molecules that are not expressed under normal circumstances and supporting the non-apoptotic nature of cell death. The broad cytotoxic response to lectins can be beneficial for the development of combination therapies targeting tumor cells. Given that tumors acquire resistance to various cytotoxic treatments because of mutations in cell death pathways, compounds inducing broad cytotoxic responses, such as lectins, represent potent sensitizers to promote tumor cell killing.